Serum IL-13 levels at diagnosis and remission in children with malignant lymphoma - Özyörük, Derya; Yavuz, Gülsan; Dinçaslan, Handan; Cabı-Unal, Emel; Taçyıldız, Nurdan; Karataş, Deniz; Doğu, Figen; İkincioğulları, Aydan (The Turkish Journal of Pediatrics, 2016)
Interleukin (IL)-13 has been reported to have a role in the pathogenesis of lymphoma through recent molecular studies predominantly in adult patients. As malignant lymphomas in children differ from adult counterparts in terms of histology and response to treatment, we aimed to determine the serum IL-13 levels of patients with lymphoma; its relation with clinical-laboratory parameters and to look for any correlation of serum IL-13 levels with different prognostic factors in children. Twenty-eight patients with malignant lymphoma and 20 age-matched healthy controls were included in the study. The median serum IL-13 level at diagnosis (range 0.59-68 pg/ml, median 3.40 pg/ml) was higher than that in remission (range 0.14-12.2 pg/ml, median 1.60 pg/ml) in the HL group (p < 0.05). Remarkably, median serum IL-13 level of patients with nodular sclerosis at diagnosis was higher than those with mixed-cellularity (p < 0.05) and declined to normal limits during remission (p < 0.05). In Burkitt’s lymphoma (BL) subgroup, the median (range 2.94-154 pg/ml, median 4.5 pg/ml) was high and declined to normal levels during remission (range 0.55-11.30 pg/ml, median 1.57 pg/ml) and the difference was significant (p < 0.05). In terms of prognostic factors, serum IL-13 levels were found to be associated with white blood cells counts only in HL group. Although the number of patients is limited in our study, we found that the serum IL-13 levels exhibit variances in different histopathologic groups. IL-13 might have a role in histopathogenesis of lymphoma, but seems to have no prognostic significance. Nevertheless, more molecular studies are needed to evaluate the pathogenesis of HL.